Thermal‐induced dielectric response in mechanically durable polyvinylidene fluoride–kapok encapsulated polyethylene glycol composite films. Issue 6 (9th April 2022) - Gong, Yutie; Li, Zhenzhen; Li, Hairong; Wu, Wenqi; Pei, Xianglin; Tu, Junyang; Zhou, Weijie; Jiang, Ming; Gong, Wei
Abstract: Dielectric materials with thermally responsive property are being pursued in fields such as next‐generation sensors, smart switches, and novel actuators. These applications require that the dielectric materials have mechanical durability and stable serviceability besides thermally responsive dielectric behavior. Herein, we report a novel thermally responsive, mechanically durable, and low‐cost dielectric composite simply fabricated by vacuum impregnating polyethylene glycol (PEG) into kapok fiber and compounding them with polyvinylidene fluoride. A remarkable dielectric susceptibility, controlled dielectric transition temperature, and obvious thermal hysteresis of the composite films induced by the solid–liquid phase transition of PEG are demonstrated. The effect of molecular weights of PEG on the dielectric response behaviors is evaluated. Such thermally responsive dielectric materials with satisfactory mechanical durability will offer a chance toward constructing thermally responsive systems for reliable and stable operation. Abstract : A novel thermally responsive, mechanically durable, and low‐cost polyvinylidene fluoride/kapok fiber/polyethylene glycol (PVDF/KF/PEG) dielectric composite is reported. A remarkable dielectric susceptibility, controlled dielectric transition temperature, and obvious thermal hysteresis of the composite films induced by the solid–liquid phase transition of PEG are demonstrated. Such thermally responsive dielectric materials with satisfactory mechanical durability will offer a chance toward constructing thermally responsive systems for reliable and stable operation.